Література та культура Полісся. – Вип. 84 - (:unkn) unknown (My University, 2016)
Literature and Culture of Polissya. – Vol. 84. Series "Philology Research". – № 7 / editor-in-chief H. V. Samoylenko. – Nizhyn : NDU named after N. Gogol, 2016. – 353 p.